Writing living heritage? Uses and misuses of transforming cultural practices into cultural texts - Sa Rego, J.; Volanska, L (SIEF2025: Unwriting, 2025)
Writing is a primary form and formality of heritage-making in both ethnographically based research and cultural policy. What are the professional and ethical norms and solutions to better embody representations of living heritage grounded in scholarship within official texts?